Assessment of the endogenous antioxidant potential of Belarusian beers during its storage in different packaging - Rusakovich, Alina A.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2024)
During long-term storage, oxidative processes develop in beer, leading to a deterioration in the quality of this drink. This is based on the production of reactive oxygen species, which can be caused by the diffusion of oxygen through packaging elements or transformation of internal oxygen-containing sources. Electron paramagnetic resonance (EPR) spectroscopy has been actively used in recent years to analyse free radical processes in beer. It allows to evaluate the oxidative stability of beer by the so-called endogenous antioxidant potential, the value of which correlates with storage time and taste of the drink. One of the most important issues in the beer industry is the effectiveness of various types of insulating packaging in relation to oxidative processes. There are a number of studies indicating better preservation of beer in a can and glass bottle compared to a polyethylene bottle. However, it is not clear whether this is due to oxidative phenomena. In the presented work, using adapted EPR spectroscopy methods based on the EPR spectrometer manufactured in Belarus, differences in the value of endogenous antioxidant potential were identified for both different types of beer and different types of packaging (polyethylene bottle, glass bottle and can). Beer stored in a polyethylene bottle has been shown to have a significantly lower endogenous antioxidant potential compared to beer stored in a glass bottle. It was also found that the oxidation characteristics of the same type of beer stored in a can and a glass bottle do not differ.
Keywords: electron paramagnetic resonance; spin traps; free radicals; beer oxidation